Visual rhetoric and cinemas of the non-Western world: Mapping cultural identity in gendered images from Egyptian and Emirati popular film - Ashour, Montiana Bahgat (AUC Knowledge Fountain, 2017)
This qualitative paper explores the gendered concept of cultural identity in non-Western popular film, through a synthesized lens of visual rhetoric and cultural studies. The term non-Western is of limited presence in film scholarship, and existing literature on popular film from non-Western geographies, is primarily interested in reading a national definition of identity through the non-Western cinematic lens. Building towards an inductive process of theory building, qualitative features of interest and intensity determine the paper's purposive selection of its two film cases, which become cinematic grounds for the exploration of a cultural dimension of identity: Molasses (Êswid, 2010); Egypt, and From A to B (Minlifly BaÊ, 2014); The United Arab Emirates. Both, Metz's cinematographic fact and the cultural lens of postcolonial masculinities, delineate the theoretical framework upon which cinematic images from both cases are observed for analysis and discussion. The paper's theorization proposes an aestheticization of culture through a masculine appearance, where the non-Western male exhibits a palliative masculinity; a "screenulinity", that sustains the cinematic popularization, as opposed to the realization, of cultural dichotomy. Thus marking the celebrated consumption of a postcolonial image-commodity of the non-Western male, and his binary cultural verisimilitude in film.